[PP.07.04] TRANSCRIPTIONAL REGULATION OF THE UMOD PROMOTER SNP RS4997081 IS SALT DEPENDENT: IMPLICATIONS FOR SODIUM HOMEOSTASIS AND BLOOD PRESSURE REGULATION. (September 2016) - Graham, L.; Fraser, N.J.; Ferreri, N.R.; Graham, D.; Dominiczak, A.F.; McBride, M.W.; Padmanabhan, S.
Abstract : Objective: We have identified a SNP (rs4997081) in the human UMOD promoter that causes elevated UMOD expression, is responsive to salt and is in LD with rs13333226 (the discovery SNP in a previous GWAS of blood pressure extremes). Previously, we have reported that UMOD regulates sodium-uptake in the thick ascending limb of the loop of Henle (TAL) by down-regulating NKCC2 expression in a TNFa dependent mechanism. The aim of the current study was to functionally assess rs4997081 promoter. Design and method: rs4997081 genotype was determined in two human renal cell lines; TK-10 (CC, risk allele) and ACHN (GG, protective allele). Promoter constructs were generated in pGL4.10 luciferase vectors and transfected into primary rodent TAL cells. Dual luciferase assays were performed to assess promoter activity of both the risk and protect allele constructs. Subsequently, the effects of exogenous TNFa (1 nM), NaCl (300 mOsmol), etanercept (10 mg/ml), TNFa siRNA and a NFkB inhibitor on the promoter activities of both risk and protect constructs were assessed. Results: Under basal conditions, the risk construct had increased promoter activity compared to the protect allele. Furthermore, treatment of TAL cells with both NaCl and TNFa was found to further enhance promoter activity at the rs4997081 risk (2.5 and 3.1 fold respectively, ***p < 0.0001) but not protect allele. The elevated promoter activity of the risk construct could be reduced to the levels observed for the protect construct by treatment with etanercept, TNFa siRNA or the NFkB inhibitor. Conclusions: Our data suggests that rs4997081 is a causal variant in the human UMOD promoter linked with increased UMOD expression at the surface of TAL cells, which causes augmented sodium reabsorption. Furthermore, we show that transcriptional activity of the major risk allele of rs4997081 is salt and TNFa dependent, suggesting that they may be physiologically important determinants of UMOD expression in vivo.